New Frontiers in Conflict Management, Peace Economics and Peace Science - Chatterji, Madhumita (Contributions to Conflict Management, Peace Economics and Development Ser., 2021)
This volume will improve our collective understanding of how to fight humanity's persistent and tragic problems with conflicts, climate shocks and disasters. The authors of this volume will offer deep insights, from their research, into the nature of evolving challenges to both global and local sustainability.